The Effect of School Leadship on Student’s Academic Achievement: Case Study Bosaso Secondary Schools in Puntland - Jama, Ibrahim Aden (Journal Evaluation in Education (JEE), 2023)
Purpose of the study: This study investigated the influence of leadership styles on secondary school student’s academic achievement in Bosaso, Somalia. Tasks were to: explore the commonly used leadership style that can lead to students’ academic performance and to establish the relationship between school heads’ leadership styles and students’ academic performance.Methodology: This study employed correlation research designed was collected through questionnaires. The data collected were analyzed by using SPSS.Main Findings: The results established that democratic leadership styles primarily influence students' academic achievement/performance, implying a strong and positive influence and significance of democratic leadership style on students' academic achievement. For the Laissez-faire leadership style, the relationship negatively influenced students' academic performance and was very weak and insignificant. Autocratic leadership style, although the relationship was powerful the relationship.Novelty/Originality of this study: In this case, it can be concluded that democratic leadership styles primarily influence students' academic achievement/performance, implying a strong and positive influence and significance of democratic leadership style on students' academic achievement.